EquiSim: An Open-Source Articulatable Statistical Model of the Equine Distal Limb - Van Houtte, Jeroen; Vandenberghe, Filip; Zheng, Guoyan; Huysmans, Toon; Sijbers, Jan (Frontiers in Veterinary Science, 2021)
Most digital models of the equine distal limb that are available in the community are static and/or subject-specific; hence they have limited applications in veterinary research. In this paper, we present a dynamic model of the entire equine distal limb, based on statistical shape modeling. The model describes the inter-subject variability in bone geometry while maintaining proper jointspace distances to support model articulation towards different poses. Shape variation modes are explained in terms of common biometrics in order to ease model interpretation from a veterinary point of view. The model is publicly available through a graphical user interface (https://github.com/jvhoutte/equisim), in order to facilitate future digitalisation in veterinary research, like computer aided designs, 3D printing of bone implants, FEM analyses for bone fracture risk assessments and data registration and segmentation problems for clinical practices.